The Effect of Plant Quality on Survival of Lymantria dispar L. (Lepidoptera: Lymantriidae) Larvae Infected by Nucleopolyhedrovirus (Journal of the Entomological Research Society, 2017)
In this study the influence of plant protein and secondary compounds on the survival rate of Lymantria dispar L. which was infected with Lymantria dispar nucleopolyhedrovirus (LdNPV), was investigated by using four different plant species, Elaeagnus rhamnoides (L.) A. Nelson, Quercus cerris L. 1753, Corylus maxima Mill. and Crataegus monogyna Jacq. The highest survival rate has been observed on the larvae feeding on the E. rhamnoides (L.) A. Nelson that had the highest protein rate. On the other hand, the highest mortality rate was recorded on the larvae which fed on the C. monogyna Jacq. containing the lowest protein rate. We have also discovered that the survival rate was related to gallotannin amounts. The survival rates of the infected larvae which fed on E. rhammoides (L.) A. Nelson with the highest gallotannin amount were higher than the other diets. Our results showed that the survival rates in the larvae infected with Lymantria dispar nucleopolyhedrovirus were positively related to the proanthocyanidin (condensed tannin) and total phenolic content of foods.
Keywords: Lymantria dispar; nucleopolyhedrovirus; secondary compounds; insect survival; mortality.